Southeast Asian Regional Port Development : A Comparative Analysis - Chia, Lin Sien (Book collections on Project MUSE., 2003)
This book provides an understanding of the dynamic regional play in terms of port development in Southeast Asia in the medium term. It presents a computer-based comparative analysis of container flows and transhipment within this region. The study provides a well-considered statistical dissection of the key port players in this part of the world - an analysis of value to businessmen, policy-makers, and observers of Southeast Asian affairs ...